2018
DOI: 10.1128/jb.00691-17
|View full text |Cite
|
Sign up to set email alerts
|

The Nitrogen Regulatory PII Protein (GlnB) and N -Acetylglucosamine 6-Phosphate Epimerase (NanE) Allosterically Activate Glucosamine 6-Phosphate Deaminase (NagB) in Escherichia coli

Abstract: Amino sugars are good sources of both ammonia and fructose-6-phosphate, produced by the glucosamine 6-phosphate deaminase, NagB. NagB is known to be allosterically regulated by -acetylglucosamine 6-phosphate (GlcNAc-6P) and the phosphocarrier protein of the bacterial phosphotransferase system, HPr, in We provide evidence that NanE, GlcNAc-6P epimerase, and the uridylylated PII protein (U-PII) also allosterically activate NagB by direct protein-protein interactions. NanE is essential for neuraminic acid (NANA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Our integral membrane interactome data suggested that many membrane proteins interact with many other membrane proteins, with a wide range of affinities [1]. Some of the high scoring interactions are likely to be permanent, high affinity interactions, while lower scoring interactions are more likely to be transient in nature [35, 36]. Among the observed interactions were many involving Enzyme IIC constituents of the PTS, particularly the fructose IIC protein, FruA, which also bears two additional domains, IIB and IIB′, where IIB′ is not involved in phosphoryl transfer, but plays a role in protein-protein interactions [21] (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…Our integral membrane interactome data suggested that many membrane proteins interact with many other membrane proteins, with a wide range of affinities [1]. Some of the high scoring interactions are likely to be permanent, high affinity interactions, while lower scoring interactions are more likely to be transient in nature [35, 36]. Among the observed interactions were many involving Enzyme IIC constituents of the PTS, particularly the fructose IIC protein, FruA, which also bears two additional domains, IIB and IIB′, where IIB′ is not involved in phosphoryl transfer, but plays a role in protein-protein interactions [21] (Table 2).…”
Section: Introductionmentioning
confidence: 99%
“…The cultures were incubated at 24 o C overnight with continuous shaking, and cells were collected by centrifugation. The PunR recombinant protein, containing an N-terminal 6His tag, was puri ed by Ni-chelation chromatography from the soluble fraction as described (36,37). The insoluble fraction was solubilized in 7 M urea and puri ed on a Ni-NTA minicolumn with At-buffer (50 mM Tris-HCl buffer, pH 8, 0.5 mM NaCl, 5 mM imidazole, and 0.3% Brij) with 7M urea.…”
Section: Methodsmentioning
confidence: 99%
“…We have collaboratively published evidence for the existence of a network of protein-protein interactions (the interactome) in E. coli (3). This work provided the incentive and a guide for the research reported in this and previous works describing allosteric regulatory phenomena (1,2).…”
mentioning
confidence: 89%
“…Carbon source availability is a signal for the recently identified global regulation of glycolysis and energy (ATP) balance by the phosphocarrier protein of the bacterial phosphotransferase system (PTS) HPr (1). Coregulation of carbon and nitrogen metabolism resulting, for example, in activation of glucosamine 6-P deaminase, NagB, by HPr, synergistically with uridylylated PII under limiting nitrogen conditions, is important for nutrient homeostasis (2). We have collaboratively published evidence for the existence of a network of protein-protein interactions (the interactome) in E. coli (3).…”
mentioning
confidence: 99%